2019
DOI: 10.1177/2331216519854597
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Informational Components of Speech-on-Speech Masking in Binaural Speech Intelligibility and Perceived Listening Effort

Abstract: Speech perception in complex sound fields can greatly benefit from different unmasking cues to segregate the target from interfering voices. This study investigated the role of three unmasking cues (spatial separation, gender differences, and masker time reversal) on speech intelligibility and perceived listening effort in normal-hearing listeners. Speech intelligibility and categorically scaled listening effort were measured for a female target talker masked by two competing talkers with no unmasking cues or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 45 publications
11
41
0
Order By: Relevance
“…Calculating this difference in thresholds is equivalent, in theory, to subtracting performance on an EM-only condition from performance on an EM-plus-IM condition, leaving only the effects of IM. Additional masking is a particularly meaningful metric because it compares each participant to themselves, thereby controlling for any potential influence of individual differences in performance which may be quite large in IM-dominated speech recognition tasks (cf., Clayton et al, 2016;Kidd & Colburn, 2017;Swaminathan et al, 2015) or to factors that may affect the ability to hear and use glimpses of masked speech (cf., Kidd et al, 2019). The higher levels of additional masking, in conjunction with equivalent group mean thresholds for the glimpsed speech and noise masking conditions, is consistent with the conclusion that PWA are especially adversely affected by competing talkers in "cocktail party" listening situations.…”
Section: Increased Susceptibility To Im In Pwasupporting
confidence: 80%
See 4 more Smart Citations
“…Calculating this difference in thresholds is equivalent, in theory, to subtracting performance on an EM-only condition from performance on an EM-plus-IM condition, leaving only the effects of IM. Additional masking is a particularly meaningful metric because it compares each participant to themselves, thereby controlling for any potential influence of individual differences in performance which may be quite large in IM-dominated speech recognition tasks (cf., Clayton et al, 2016;Kidd & Colburn, 2017;Swaminathan et al, 2015) or to factors that may affect the ability to hear and use glimpses of masked speech (cf., Kidd et al, 2019). The higher levels of additional masking, in conjunction with equivalent group mean thresholds for the glimpsed speech and noise masking conditions, is consistent with the conclusion that PWA are especially adversely affected by competing talkers in "cocktail party" listening situations.…”
Section: Increased Susceptibility To Im In Pwasupporting
confidence: 80%
“…Our interpretation of the results from the speech masking condition, in which masker sentences were highly similar to and confusable with target sentences, is that this condition produced high levels of IM while causing much lower levels of EM. This conclusion is based on the TMRs at threshold obtained in that condition relative to the thresholds in the glimpsed and noise masking conditions (cf., Kidd et al, 2019;Rennies et al, 2019). These results showed that thresholds in this condition were higher (worse) for PWA than for HC, suggesting that PWA speech processing abilities break down more than those of HC as levels of competing speech are increased, which in turn suggests that PWA are more susceptible to the effects of IM than are HC.…”
Section: Increased Susceptibility To Im In Pwamentioning
confidence: 78%
See 3 more Smart Citations